Haikyu!! Volume 13, Playground - Furudate, Haruichi, 1983- (VIZ Media, LLC, 2017)
Shoyo Hinata is out to prove that in volleyball you don't need to be tall to fly! Ever since he saw the legendary player known as "the Little Giant" compete at the national volleyball finals, Shoyo Hinata has been aiming to be the best volleyball player ever! He decides to join the team at the high school the Little Giant went to--and then surpass him. Who says you need to be tall to play volleyball when you can jump higher than anyone else? Karasuno fights their way through the preliminaries and wins, earning them a spot in the October qualifier rounds of the Spring Tournament. Their first opponent is a team of partyers from Johzenji whose motto is "Play hard"! They are a highly unorthodox team that improvises crazy attacks on the fly, leaving Karasuno baffled about how to counter them!